Analysis of Violations of Corporate Governance Principles in Smuggling Cases of Garuda Indonesia - Afiatika Ayyi Shawaaba; Dikrilla Sarla Maulani; Dita Ayu Nirmala; Muhammad Fauzan Abimanyu Subekti (Publica: Jurnal Pemikiran Administrasi Negara, 2022)
This study aims to analyze the violation of corporate governance principles in the smuggling case of a Harley Davidson motorcycle and two Brompton bicycles on the new Airbus A330-900 by the President Director of PT Garuda Indonesia and four other boards of directors involved in supporting it. The type of research used is qualitative research with a descriptive research design. This study focuses on analyzing an object by studying it as a case intensively. This research uses the data analysis method content analysis approach with the study documentation collection method. Research data sources were obtained from secondary data, namely by searching for previous research, the internet, financial reports from PT Garuda Indonesia, and several other reliable sources.  It can be seen from this study that the smuggling act by the former president director of PT Garuda Indonesia violated the five principles of good corporate governance.” The five principles are transparency, accountability, responsibility, independence, and fairness. These five principles must be used as guidelines for companies in carrying out their performance so that companies can operate efficiently and effectively and compete well in the market.